Petrografia e diagênese dos arenitos Neoproterozóicos da Formação Raizama, sul do Cráton Amazônico e Faixa Paraguai, Mato Grosso - SANTOS, Hudson Pereira (2019)
The end of the Neoproterozoic in the north of the Paraguay Belt and the south Amazon Craton have been intensely debated. The colision of the Amazon, São Fransisco-Congo, and the Paranapanema(?) blocks resulted in the uplift of the Paraguary-Araguaia Belt. In this context, the Raizama Formation, base of the Alto Paraguay Group and the gol of this study, is characterized by fine to coarse siliciclastic deposits, associated with the transitional deposits (fluvial with tidal influence) and shallow marine(foreshore/shoreface), which overlie the carbonate sedimentation of the Araras Group. The area of study includes the municipalities of Gloria d’Oeste, Tangará da Serra, Cáceres, Alto Paraguai and Nobres. The petrographic study of thin sections came from the north of the Paraguay Belt and the south of the Amazon Craton, permited the individualization of six lithotypes consisted as quartz-sandstone, subarkoses, dolomitic-limestone, dolomite, chert, and sublitharenites. Sandstones from Amazon Craton have late dolomite cementation, whereas the sandstones from Paraguay belt have intense quartz overgrowth. The concentration of lithic fragments fluctuate of 0,3% to 11,7% in the samples from Paraguay Belt , absent in the samples from Amazon Craton. The pattern of the QmFLt diagrams show that the Raizama Formation sediments are recycled orogen and stable continental blocks. The diagenetic processes that intergrate the diagenetic sequence are: 1) authigenic clay minerals; 2) mechanical compaction; 3) quartz overgrowth; 4) pressure solution; 5) replacement and/or solution of quartz; and 6) dolomization. The study of the Raizama Formation sandstones enable a better understanding of the diagenetic processes by which these rocks have been subjected, contributing to the characterization of the Alto Paraguay Group, which has not been studied much.